Sistem Informasi Penerimaan Donasi Zakat, Infaq dan Sedekah (ZIS) pada Etalase Sedekah Kota Padang Berbasis Web Framework Laravel - Indra Zandi; Yance Sonatha; Fitri Nova (SOTVI - Society of Visual Informatics, 2022)
The Sedekah Showcase is one of the organizations that organizes donations where this institution provides a forum for the community to distribute donations, which will later be distributed to the people in need who are registered. In analyzing the Donation Information System and ZIS (Zakat, Infaq, Alms) there are 6 aspects of system analysis needed, namely Performance (Performance), Information (Information), Economy (Economic), Control (Control), Efficiency (Efficiency), and Service ( services). In the donation information system and ZIS Etalase Sedekah, the actors involved are system administrators, donors, and volunteers. Information System for Receiving Donations and Zakat, Infaq and Alms (ZIS) at the Sedekah Showcase of Padang City Based on the Laravel Web Framework includes management of receiving donations and ZIS transactions as well as transaction history, periodic reporting of transactions, surveys of Beneficiaries, data management of Donors, Volunteers , and Beneficiaries. PHP programming language using Laravel framework and database using MySQL and using DOMPDF in designing e-reports.